Estudo semiótico dos vínculos afetivos na campanha presidencial de Lula no Instagram em setembro de 2022 - Yang, Michele Miyuki (2023)
Using Luiz Inácio Lula da Silva's campaign for the presidency of Brazil in 2022 as a corpus for analysis, this research focuses on the trajectory of affective elements related to Lula's campaign speeches and the corresponding emotional effects produced to win the support of undecided voters and those dissatisfied with other candidates. In other words, it aims to investigate how Lula and his party, on the eve of the first round of the 2022 elections, employed Instagram as a strategic instrument to attract and emotionally engage the right-wing and centrist voters and identify which emotions were involved. Using Laclau and Mouffe's discourse analysis methodology to map the speeches and Greimas and Fontanille's Semiotics of Passions to study the emotions, the most frequently observed strategy was the "useful vote", which relied on the theme of "Brazil of Hope" to make an impact. Both the strategy and the theme were explored, followed by a general discussion of their implications on the results. The choice to collect publications during the 15 days preceding the first round was largely due to the proximity to the presidential elections, considering the increasing antagonism towards Bolsonarism and the dissemination of fake news circulating on the internet. The analysis results showed that, during the selected period for corpus formation, the main emotions mobilized were complex passions such as satisfaction and indignation